Epidemiology and nosocomial infection control in a pediatric unit - Silva, Rafael Souza; Oliveira, Adriana Cristina (Revista de Enfermagem UFPE on line, 2008)
ABSTRACT This research aimed at determining the pediatric patients profile at a School- Hospital, according to the variables sex, age, patients lenght-of stay, colonizing/infecting microorganisms, nosocomial infections (NI) and patiens outcomes. This was a prospective and descriptive epidemiological study developed in 2006 to which a database was developed in the SPSS program so as to type datas and analysed them afterwards. It was identified 668 patients, from whom, 53,7% were male, global avarage age was 5,1 years old and lenght-of-stay avarage was 10,1 days. It was colonized by resistant microorganisms 4,2% of the patients and 7,5% developed NI, being sepsis them most recurrent and Staphylococcus epidermides and Cândida albicans the most evident microorganisms. There were 98,5% of discharge and 1,5% of deaths. This study reinforces the needing for continuous/active NI surveillance programes and the identification of (re) emergence of resistant bacterias so as to direct NI prevention and controle measures by those microorganisms. Descriptors: nosocomial infections; pediatrics; resistance; drug; children. RESUMO Objetivou-se com este estudo determinar o perfil dos pacientes pediátricos de um Hospital Universitário, conforme o sexo, idade, tempo de internação, microrganismos colonizantes/infectantes, infecções hospitalares (IH) e desfecho dos mesmos. Tratou-se de um estudo epidemiológico descritivo, realizado em 2006, para o qual foi elaborado um banco de dados no programa SPSS para a digitação dos dados e posterior análise estatística descritiva. Identificaram-se 668 pacientes, sendo 53,7% do sexo masculino, a média de idade global de 5,1 anos e o tempo médio de internação de 10,1 dias. Foram colonizados por microrganismos resistentes 4,2% dos pacientes e 7,5% desenvolveram IH, sendo as sepses mais recorrentes e o Staphylococcus epidermides e Cândida albicans os microrganismos mais prevalentes. Houve 98,5% de altas e 1,5% de óbitos. Reforça-se a necessidade de programas de vigilância contínua/ativa de IH e a identificação da (re) emergência de bactérias resistentes a fim de direcionar medidas de prevenção e controle de IH por estes microrganismos. Descritores: infecção hospitalar; pediatria; resistência; drogas; criança. RESUMEN El presente estudio determinó el perfil de los pacientes pediátricos de un Hospital Universitario, según las variables sexo, edad, tiempo de internación, microorganismos colonizadores/infectantes, infecciones hospitalarias (IH) y finalización de los mismos. Se trata de un estudio epidemiológico realizado en 2006. Se realizó una análisis estadística descriptiva utilizando el programa SPSS. Se identificaron 668 pacientes, siendo 53,7% del sexo masculino, con una media de edad global de 5,1 años y tiempo de internación de 10,1 días. Fueron colonizados por microorganismos resistentes 4,2% de los pacientes y 7,5% desarrollaron IH, siendo as sepses más frecuentes y el Staphylococcus epidermides y Candida albicans los microorganismos más prevalecientes. Hubo 98,5% de altas y 1,5% de fallecimientos. Se refuerza la necesidad de programas de vigilancia continua/activa de IH y la identificación de la (re) emergencia de bacterias resistentes con el objetivo de orientar medidas de prevención y control de IH por estos microorganismos. Descriptores: infección hospitalaria; pediatría; resistencia; drogas; niños.